Seroprevalance And Molecular Detection Of Fmdv In Cattle At Savar In Bangladesh - Jannat, N; Rahman, MS; Islam, E; Rumi, NA; Giasuddin, M; Hasan, M; Islam, MR; Hassan, MZ (SAARC Journal of Agriculture, 2020)
The study was conducted to observe the overall seroprevalence and molecular detection of circulating FMD virus from infected cattle and efficacy of antibacterial drugs against secondary bacterial infection at Savar, Dhaka from January- December 2018. A total of 92 serum samples were collected for indirect c-ELISA to detect antibodies against non-structural proteins of FMD virus, and overall seroprevalence was 94.02%. The seroprevalence of serotype O and A was higher (95.83% and 95.83%) in male cattle than female (93.18% and 90.91%) respectively. 6 Months to 3 years aged cattle showed, significantly (p<0.01) higher seroprevalence (100%) than above 4 years age groups for serotype O (82.14%) and A (78.57%). Local cattle were more seropositive 96.88% compared to crossbred cattle 93.33% for serotype O and 91.67% for serotype A and this variation was not statistically significant (p>0.05). Among 10 clinical samples of FMD from infected cattle, 8 samples were positive for different serotypes, among them 2 each were identified as serotype A and Asia-1. On the other hand,4 samples were identified as mixed infection (1 sample of serotype O+A, 3 samples of O+Asia-1) by mRT-PCR. In this study on therapeutic intervention with sulphadimidine significantly (p<0.05) reduced the clinical signs of FMD than Gentamycin and Ampicillin. The higher seroprevalence of the disease has substantial economic implications which signify the need for devising effective control measure. However, the detection of ‘O’, Asia-1and ‘A’ serotype emphasizes the critical need for use of atrivalent vaccine in the field. SAARC J. Agri., 17(2): 67-78 (2019)